2014
DOI: 10.1063/1.4883475
|View full text |Cite|
|
Sign up to set email alerts
|

Quasi-Moseley's law for strong narrow bandwidth soft x-ray sources containing higher charge-state ions

Abstract: Bright narrow band emission observed in optically thin plasmas of high-Z elements in the extreme ultraviolet spectral region follows a quasi-Moseley's law. The peak wavelength can be expressed as λ=(21.86±12.09)×R∞−1×(Z−(23.23±2.87))−(1.52±0.12), where R∞ is the Rydberg constant. The wavelength varies from 13.5 nm to 4.0 nm as the atomic number, Z, increases from Z = 50 to Z = 83. The range of emission wavelengths available from hot optically thin plasmas permits the development of bright laboratory-scale sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…Optically thinner LHD plasma spectra are shown in Figures 6(l) −6(q). It should be noted that the electron temperatures of LHD plasma were relatively low, ≤ 1 keV, but higher than in 150-ps LPPs [24].…”
Section: N+1mentioning
confidence: 99%
See 1 more Smart Citation
“…Optically thinner LHD plasma spectra are shown in Figures 6(l) −6(q). It should be noted that the electron temperatures of LHD plasma were relatively low, ≤ 1 keV, but higher than in 150-ps LPPs [24].…”
Section: N+1mentioning
confidence: 99%
“…In this section, we show that the strong resonance UTAs of Nd:YAG LPPs for elements with Z = 50−83 obey a quasi-Moseley's law [24]. A 150-ps Nd:YAG laser with a maximum energy of 250 mJ at λ L = 1.064 μm and an 8-ns Nd:YAG laser giving 400 mJ at λ L = 1.064 μm were employed to provide the desired variation of laser intensity.…”
Section: Quasi-moseley's Law For the Uta Emissionmentioning
confidence: 99%
“…When the outer diameter of the thick-shell type TESPEL is around 700 µm, the shell thickness of the TESPEL is usually about 250 µm. In this case, the total amount of the electron and ion in the shell are 6.0 × 10 19 and 1.7×10 19 , respectively. Since the typical volume of the LHD plasma is 30 m 3 , the ratio of the numbers of the electron from this thick-shell type TESPEL to that of the LHD plasma is only 6.7% in the case of the averaged bulk electron density of 3 × 10 19 m −3 .…”
Section: Various Types Of Tespelsmentioning
confidence: 95%
“…The photograph clearly shows the bulged tiny polystyrene ball from the surface of the TESPEL as described above. For reference, the photograph of the Au-containing conventional (thick-shell type) TESPEL, which is used for the development research of an extreme ultraviolet lithography light source [19], is also shown in Fig. 4 (b).…”
Section: Various Types Of Tespelsmentioning
confidence: 99%
“…[2][3][4] The wavelength of the UTA emission from a near Pd-like ion of heavy elements decreases according to the quasi-Moseley's law to λ = 3.97 nm using Bi. 5 The emission at λ = 6.x nm from Gd and Tb 6 is considered a candidate source for future microlithography. 7 Light sources at the waterwindow wavelengths, λ = 2.4 -4.5 nm, have attracted attention for biological imaging.…”
Section: Nm To the Water Window © 2016 Author(s) All Article Contenmentioning
confidence: 99%